2005
DOI: 10.1099/vir.0.80975-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and subcellular localization of transmissible gastroenteritis virus nucleocapsid protein in infected cells

Abstract: The nucleocapsid (N) protein is the only phosphorylated structural protein of the coronavirus Transmissible gastroenteritis virus (TGEV). The phosphorylation state and intracellular distribution of TGEV N protein in infected cells were characterized by a combination of techniques including: (i) subcellular fractionation and analysis of tryptic peptides by two-dimensional nano-liquid chromatography, coupled to ion-trap mass spectrometry; (ii) tandem mass-spectrometry analysis of N protein resolved by SDS-PAGE; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
2
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 55 publications
0
52
2
2
Order By: Relevance
“…It has been reported that the N proteins of MHV and IBV localized in the nucleolus of a small number of infected cells (Wurm et al, 2001). TGEV N protein was not observed in the nucleolus of infected ST cell lines (Calvo, 2005). In the case of our study, PEDV N protein was not observed in the nucleolus of the cells by confocal microscopy.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been reported that the N proteins of MHV and IBV localized in the nucleolus of a small number of infected cells (Wurm et al, 2001). TGEV N protein was not observed in the nucleolus of infected ST cell lines (Calvo, 2005). In the case of our study, PEDV N protein was not observed in the nucleolus of the cells by confocal microscopy.…”
Section: Discussioncontrasting
confidence: 56%
“…We did not detect any difference in phosphorylation of the protein from the infected cells and that in extracellular virions. Calvo et al (2005) suggested the possibility that phosphorylation/ dephosphorylation could play a role in TGEV assembly. The details of virus release are not fully understood, but virions are thought to transport through the constitutive secretory pathway after budding.…”
Section: Discussionmentioning
confidence: 99%
“…Representative SDS-PAGE used to isolate MHV N protein and peptide map coverage. Positions of the phosphorylated sites on MHV N, conserved resides in the group II viruses BCoV, HCoV OC43 and SARS CoV, and recently identified sites on IBV (Chen et al, 2005) and TGEV (Calvo et al, 2005) N proteins are highlighted. Boxes indicate the areas of gel excision.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal domain contributes to its di-or multimerization assembly (13,14), and the central region contains a serine/ arginine (SR)-rich motif with unknown function but which is possibly also involved in the regulation of its multimerization (15). Notably, N proteins are highly phosphorylated in infected cells (16,17). Surjit et al (18) provided evidence that SCoV N protein undergoes phosphorylation in cells, mainly at the serine residues.…”
mentioning
confidence: 99%